Possible molecular basis of the biochemical effects of cysteine-derived persulfides - Cuevasanta, Ernesto; Benchoam, Dayana; Semelak, Jonathan A.; Möller, Matías N.; Zeida, Ari; Trujillo, Madia; Alvarez, Beatriz; Estrin, Darío A. (Frontiers in Molecular Biosciences, 2022)
Persulfides (RSSH/RSS-) are species closely related to thiols (RSH/RS-) and hydrogen sulfide (H2S/HS-), and can be formed in biological systems in both low and high molecular weight cysteine-containing compounds. They are key intermediates in catabolic and biosynthetic processes, and have been proposed to participate in the transduction of hydrogen sulfide effects. Persulfides are acidic, more acidic than thiols, and the persulfide anions are expected to be the predominant species at neutral pH. The persulfide anion has high nucleophilicity, due in part to the alpha effect, i.e., the increased reactivity of a nucleophile when the neighboring atom has high electron density. In addition, persulfides have electrophilic character, a property that is absent in both thiols and hydrogen sulfide. In this article, the biochemistry of persulfides is described, and the possible ways in which the formation of a persulfide could impact on the properties of the biomolecule involved are discussed.